The correction of Ollier’s disease induced extremities deformity using distraction osteogenesis by intralesional osteotomy in children patients: a cases series study - Lei Xu; Huijuan Song; Ying Ren; Meixin Li; Xiangqing Meng; Chunhao Zhou; Chenghe Qin (Journal of Orthopaedic Translation, 2020)
Objective: the present study was aimed at evaluating the effect of distraction osteogenesis using monolateral external fixators by intralesional osteotomy in children patients of Ollier’s disease. Methods: 2 male and 4 female children patients of Ollier’s disease with an average age of 7.8 years received treatment between 2008 and 2016 were included in the study, and 1 ulna, 3 femurs, 4 tibias, 1 radius, and 1 humerus were involved. The Ollier’s disease induced extremities’ deformities were corrected by distraction osteogenesis using monolateral external fixator (LRS), and the intralesional osteotomy was conducted. The original length and the distracted length, the severity of angular deformity, and the mechanical axis deviation of the affected bones were measured. The initial and ending dates of bone lengthening, as well as the installation date and removal date of frames were recorded. The distraction index (DI) and the external fixator index (EFI) were calculated. Postoperative follow-up efficacy was assessed by regular radiographic examinations. Results: after treatment in all cases the length discrepancy of the affected limbs with contralateral side were less than 3 ​cm, and the angular deformities were corrected. The mean lengthened bones were 52.8 ​mm ​± ​14.9 ​mm, the average DI was 12.9 days/cm ± 1.6 days/cm, and the mean EFI was 50.5 days/cm ± 12.5 days/cm. Pain as the complication were found in all cases and was managed by analgesics. Pin site infection were reported in one case and was cured by wound care and normal use of antibiotics. One case was found to have delayed bone healing but the volume and size of the affected bone was recovered to normal about 3 months after removal of the frames. Conclusion: this study revealed that distraction is beneficial for the conversion of enchondromal bone into normal bone, and intralesional osteotomy is safe and supposed to protect the remaining healthy bone segment. Taken together, distraction osteogenesis using monolateral external fixators is effective in managing the length and angular deformity of extremities caused by Ollier’s disease in children patients.The translational potential of this article: To date, no consensus for the correction of extremities deformity induced by the Ollier’s disease has been established. This study found that distraction as a treatment could promote conversion of enchondromal bone into normal bone, and intralesional osteotomy is safe and beneficial for saving the limited healthy bone on the whole bone segment from being iatrogenically damaged. Such findings will provide some references for the treatments of extremities.